Safety and efficacy of salvage endoscopic submucosal dissection for Barrett’s neoplasia recurrence after radiofrequency ablation - Mesureur, Lauriane; Deprez, Pierre H.; Bisschops, Raf; Pouw, Roos E.; Weusten, Bas L.A.M.; Barret, Maximilien; Dewint, Pieter; Tate, David; Leclercq, Philippe; Seewald, Stefan; Barbaro, Federico; Baldaque-Silva, Francisco; Omae, Masami; Pioche, Mathieu; Figueiredo Ferreira, Mariana; Bourke, Michael J.; Haidry, Rehan; Snauwaert, Christophe; Eisendrath, Pierre; De Maertelaer, Viviane; Rosewick, Nicolas; Devière, Jacques; Lemmers, Arnaud (Endoscopy, 2024)
Background This study evaluated the safety and efficacy of salvage endoscopic submucosal dissection (ESD) for Barrett’s neoplasia recurrence after radiofrequency ablation (RFA).Methods Data from patients at 16 centers were collected for a multicenter retrospective study. Patients who underwent at least one RFA treatment for Barrett’s esophagus and thereafter underwent further esophageal ESD for neoplasia recurrence were included.Results Data from 56 patients who underwent salvage ESD between April 2014 and November 2022 were collected. Immediate complications included one muscular tear (1.8%) treated with stent (Agree classification: grade IIIa). Two transmural perforations (3.6%; treated with clips) and five muscular tears (8.9%; two treated with clips) had no clinical impact and were not considered as adverse events. Seven patients (12.5%) developed strictures (grade IIIa), which were treated with balloon dilation. Histological analysis showed 36 adenocarcinoma, 17 high grade dysplasia, and 3 low grade dysplasia. En bloc and R0 resection rates were 89.3% and 66.1%, respectively. Resections were curative in 33 patients (58.9%), and noncurative in 22 patients (39.3%), including 11 “local risk” (19.6%) and 11 “high risk” (19.6%) resections. At the end of follow-up with a median time of 14 (0–75) months after salvage ESD, and with further endoscopic treatment if necessary (RFA, argon plasma coagulation, endoscopic mucosal resection, ESD), neoplasia remission ratio was 37/53 (69.8%) and the median remission time was 13 (1–75) months.Conclusion In expert hands, salvage ESD was a safe and effective treatment for recurrence of Barrett’s neoplasia after RFA treatment.